Characterization and clinical significance of the CADM1/HER2/STAT3 axis in serous ovarian tumors. Issue 8 (26th February 2021) - Wu, Dan; Lei, Yuzhou; Liu, Qin; Hu, Hua; Li, Huanhuan; Xie, Lin; Zhou, Jianbin
Abstract : Abstract: The subtypes of serous ovarian tumors (SOTs), including benign serous cystadenoma, serous borderline tumor (SBT), low-grade serous ovarian carcinoma (LGSC), and high-grade serous ovarian carcinoma (HGSC), remain poorly understood. Herein, we aimed to characterize the cell adhesion molecule 1 (CADM1)/signal transducer and activator of transcription 3 (STAT3)/human epidermal growth factor receptor 2 (HER2) axis and identify its clinical significance in patients with serous cystadenoma, SBT, LGSC, and HGSC. The immunohistochemical expression of CADM1, HER2, and STAT3 was assessed in 180 SOT specimens, and its association with clinical data was determined. High levels of CADM1 expression were detected in 100% of serous cystadenomas and 83.33% of SBTs, while a loss of CADM1 expression was observed in 44% of LGSCs and 72.5% of HGSCs. Relative to the levels in benign cystadenomas and SBTs, higher levels of HER2 and STAT3 expression were observed in LGSCs and aggressive HGSCs. Furthermore, the expression profile of the CADM1/HER2/STAT3 axis was significantly associated with histologic type, International Federation of Gynecology and Obstetrics stage, and lymph node metastasis in patients with SOT. Our study identified the changes in the CADM1/HER2/STAT3 axis that were closely associated with the clinical behavior of SOTs. These molecular data may provide new insights into SOT carcinogenesis and aid in the diagnosis and treatment of patients with SOT.